1995
DOI: 10.1029/94ja03233
|View full text |Cite
|
Sign up to set email alerts
|

On the propagation of transversally small‐scale standing Alfven waves in a three‐dimensionally inhomogeneous magnetosphere

Abstract: In terms of a three‐dimensionally inhomogeneous model of the magnetosphere, we have investigated theoretically the process of propagation across the geomagnetic field of monochromatic standing Alfven waves that are transversally small‐scale ones. For this purpose we introduced an orthogonal coordinate system tied in a natural manner to the geomagnetic field. It is shown that a three‐dimensionally inhomogeneous magnetosphere is composed of sectors that differ from each other by the propagation character of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 14 publications
3
42
0
1
Order By: Relevance
“…In the course of the propagation the polarization of the Alfve n wave changes from radial (poloidal) to azimuthal (toroidal). An extension of this theory is reported by Leonovich and Mazur (1995a,b) and Klimushkin et al (1995). This theory is, we believe, a realistic theory for small-scale hydromagnetic waves in cold regions of the magnetosphere; however, the main merit of Paper I is a mathematical theory of WKB-approximation for a two-dimensionally inhomogeneous plasma.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the course of the propagation the polarization of the Alfve n wave changes from radial (poloidal) to azimuthal (toroidal). An extension of this theory is reported by Leonovich and Mazur (1995a,b) and Klimushkin et al (1995). This theory is, we believe, a realistic theory for small-scale hydromagnetic waves in cold regions of the magnetosphere; however, the main merit of Paper I is a mathematical theory of WKB-approximation for a two-dimensionally inhomogeneous plasma.…”
Section: Introductionmentioning
confidence: 99%
“…We did not make any assumptions about FMS, but we found that the condition m ) 1 automatically entails its absence. For fast magnetosound with m ) 1 the magnetosphere is opaque; see also Walker (1987), Leonovich and Mazur (1990).…”
Section: Identifying the Alfveân And Magnetosound Branches Of Oscillamentioning
confidence: 99%
See 2 more Smart Citations
“…When studying the structure of the toroidal and poloidal modes, it is appropriate to take into account the plasma inhomogeneity not only across magnetic shells, but also in the direction along the external magnetic field, and, in addition, the field line curvature and finite plasma pressure, because all of these factors affect the difference between the frequencies of poloidal and toroidal oscillations (Krylov et al, 1981;Walker, 1987). A study of the global structure of the wave was carried out by Leonovich and Mazur (1993), Klimushkin et al (1995), Kouznetsov and Lotko (1995), Vetoulis and Chen (1996), and Klimushkin (1998a, b). However, the question still is: What are the conditions and magnetospheric regions where Alfvén waves can have particular polarization properties?…”
Section: Introductionmentioning
confidence: 99%